Determinants of authentic experiences: An extended Gilmore and Pine model for ethnic restaurants. Issue 10 (10th October 2016) - Kim, Jong-Hyeong; Jang, SooCheong (Shawn)
Abstract : Purpose: This study aims to address a lack of studies on the attributes of ethnic restaurants that influence customers' perceptions of authenticity. Particularly, this study extended Gilmore and Pine's authenticity framework (is the offering true to itself and is the offering what it says it is) by incorporating a servicescape factor (i.e. employees). Design/methodology/approach: This study used a 2 × 2 × 2 between-participants design which examined the effects of using an authentic sauce in a dish, advertising "authenticity" and employing staff from the native culture of the ethnic food on authentic experiences. Follow-up contact was made by phone and mail to assess their memory of ethnic Korean food tried in experimental conditions. Participants were asked how clearly and vividly they could recollect the food experience. Findings: The results showed that all of the tested factors significantly influenced the subjects' perceived authenticity of the food and recollection of the food experience. However, the authors did not find any significant interaction effects. Practical implications: This study suggests factors that influence customers' authentic experiences and memory. Thus, the findings provide important implications for delivering authentic and memorable experiences. Originality/value: Previous researchers have emphasized the importance and urgency of providing authentic and memorable experiences. However, it is still unclear what specific attributes of ethnic restaurants influence individuals' perceptions of authenticity and memory.